APLIKASI COOPERATIF LEARNING TIPE GROUP INVESTIGATION ( GI) PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI KELAS V FAVORIT MI SALAFIYAH SYAFI’IYAH SUKOREJO SITUBONDO, TAHUN PELAJARAN 2015/2016 - Achmad Naim (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Abstract: One of the problems that also exist in the Madrasah Ibtidaiyah in learning is learning to SKI (history of Islamic culture). This material is primarily material that is interesting, but sometimes in the pelaksanaanya become not interesting for students. This appears sometimes students don't listen well and the results of the evaluation of the results has not yet reached the target of KKM. The issues examined in this research is the application of Methods of learning Group Investigation (GI) at the basic education level students (MI). The approach used in this study is a qualitative approach to the type of this action research including research action class. Class action research design starts from the beginning to the end of the study. Based on the research results it can be concluded that with the implementation of the pembelajara cooperative Group type Investigation (GI) on subjects of history of Islamic culture goes well, students look happy, active and enthusiastic because in the process of cooperative learning Group-type Investigation (GI). Observation data analysis results are known, the application of the cooperative learning Group-type Investigation (GI) can improve learning outcomes grade V Syaf'iyah Salafiyah MI favorite Sukorejo Situbondo lessons year 2011/2012. It can be seen from the results of observations against the liveliness, the will, the ability and responsibility of students, as well as the achievement of student learning ketuntasan criteria (KKM) overall. Improvement of the learning outcomes can be seen from the value of the percentage of students with daily exams ketuntasan in classical and individual attain a value of 94%.Keywords; SKI, Cooperative learning, Group Investigation